Generation and physiological characterization of genome-edited Nicotiana benthamiana plants containing zeaxanthin as the only leaf xanthophyll - Maria Sulli; Luca Dall’Osto; Paola Ferrante; Zeno Guardini; Rodrigo Lionel Gomez; Paola Mini; Olivia Costantina Demurtas; Giuseppe Aprea; Alessandro Nicolia; Roberto Bassi; Giovanni Giuliano (Planta, 2023)
Main conclusion Simultaneous genome editing of the two homeologous LCYe and ZEP genes of Nicotiana benthamiana results in plants in which all xanthophylls are replaced by zeaxanthin . Abstract Plant carotenoids act both as photoreceptors and photoprotectants in photosynthesis and as precursors of apocarotenoids, which include signaling molecules such as abscisic acid (ABA). As dietary components, the xanthophylls lutein and zeaxanthin have photoprotective functions in the human macula. We developed transient and stable combinatorial genome editing methods, followed by direct LC–MS screening for zeaxanthin accumulation, for the simultaneous genome editing of the two homeologous Lycopene Epsilon Cyclase ( LCYe ) and the two Zeaxanthin Epoxidase ( ZEP ) genes present in the allopolyploid Nicotiana benthamiana genome. Editing of the four genes resulted in plants in which all leaf xanthophylls were substituted by zeaxanthin, but with different ABA levels and growth habits, depending on the severity of the ZEP1 mutation. In high-zeaxanthin lines, the abundance of the major photosystem II antenna LHCII was reduced with respect to wild-type plants and the LHCII trimeric state became unstable upon thylakoid solubilization. Consistent with the depletion in LHCII, edited plants underwent a compensatory increase in PSII/PSI ratios and a loss of the large-size PSII supercomplexes, while the level of PSI-LHCI supercomplex was unaffected. Reduced activity of the photoprotective mechanism NPQ was shown in high-zeaxanthin plants, while PSII photoinhibition was similar for all genotypes upon exposure to excess light, consistent with the antioxidant and photoprotective role of zeaxanthin in vivo.

Plants and water in a changing world: a physiological and ecological perspective - Roberto Caferri; Roberto Bassi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
The reduction of greenhouse gases (GHGs) emission by replacing fossil energy stocks with carbon–neutral fuels is a major topic of the political and scientific debate on environmental sustainability. Such shift in energy sources is expected to curtail the accumulation rate of atmospheric CO 2 , which is a strong infrared absorber and thus contributes to the global warming effect. Although such change would produce desirable outputs, the consequences of a drastic decrease in atmospheric CO 2 (the substrate of photosynthesis) should be carefully considered in the light of its potential impact on ecosystems stability and agricultural productivity. Indeed, plants regulate CO 2 uptake and water loss through the same anatomical structure: the leaf stomata. A reduced CO 2 availability is thus expected to enhance transpiration rate in plants decreasing their water use efficiency and imposing an increased water demand for both agricultural and wild ecosystems. We suggest that this largely underestimated issue should be duly considered when implementing policies that aim at the mitigation of global environmental changes and, at the same time, promote sustainable agricultural practices, include the preservation of biodiversity. Also, we underlie the important role(s) that modern biotechnology could play to tackle these global challenges by introducing new traits aimed at creating crop varieties with enhanced CO 2 capture and water- and light-use efficiency.

The intrusion of ecology into hydrology and morphodynamics - Roberto Bassi; Andrea Rinaldo; Giovanni Seminara (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Light-harvesting complex stress-related proteins play crucial roles in the acclimation of Physcomitrella patens under fluctuating light conditions - Shan Gao; Alberta Pinnola; Lu Zhou; Zhenbing Zheng; Zhuangyue Li; Roberto Bassi; Guangce Wang (Photosynthesis Research, 2022)

Plants with less chlorophyll: A global change perspective - Lorenzo Genesio; Roberto Bassi; Franco Miglietta (Global Change Biology, 2021)
The necessary reduction of greenhouse gas (GHG) emissions may lead in the future to an increase in solar irradiance (solar brightening). Anthropogenic aerosols (and their precursors) that cause solar dimming are in fact often co‐emitted with GHGs. While the reduction of GHG emissions is expected to slow down the ongoing increase in the greenhouse effect, an increased surface irradiance due to reduced atmospheric aerosol load might occur in the most populated areas of the earth. Increased irradiance may lead to air warming, favour the occurrence of heatwaves and increase the evaporative demand of the atmosphere. This is why effective and sustainable solar radiation management strategies to reflect more light back to space should be designed, tested and implemented together with GHG emission mitigation. Here we propose that new plants (crops, orchards and forests) with low‐chlorophyll (Chl) content may provide a realistic, sustainable and relatively simple solution to increase surface reflectance of large geographical areas via changes in surface albedo. This may finally offset all or part of the expected local solar brightening. While high‐Chl content provides substantial competitive advantages to plants growing in their natural environment, new plants with low‐Chl content may be successfully used in agriculture and silviculture and be as productive as the green wildtypes (or even more). The most appropriate strategies to obtain highly productive and highly reflective plants are discussed in this paper and their mitigation potential is examined together with the challenges associated with their introduction in agriculture.

Optimized Cas9 expression systems for highly efficient Arabidopsis genome editing facilitate isolation of complex alleles in a single generation - Jana Ordon; Mauro Bressan; Carola Kretschmer; Luca Dall’Osto; Sylvestre Marillonnet; Roberto Bassi; Johannes Stuttmann (Functional & Integrative Genomics, 2020)

Functional analysis of LHCSR1, a protein catalyzing NPQ in mosses, by heterologous expression in Arabidopsis thaliana - Ioannis Dikaios; Christo Schiphorst; Luca Dall’Osto; Alessandro Alboresi; Roberto Bassi; Alberta Pinnola (Photosynthesis Research, 2019)

Loss of LHCI system affects LHCII re-distribution between thylakoid domains upon state transitions - Mauro Bressan; Roberto Bassi; Luca Dall’Osto (Photosynthesis Research, 2018)

Antenna size reduction as a strategy to increase biomass productivity: a great potential not yet realized - Tim de Mooij; Marcel Janssen; Oscar Cerezo-Chinarro; Jan H. Mussgnug; Olaf Kruse; Matteo Ballottari; Roberto Bassi; Sandrine Bujaldon; Francis-André Wollman; René H. Wijffels (Journal of Applied Phycology, 2015)

Post-transcriptional control of light-harvesting genes expression under light stress - Maïna Floris; Roberto Bassi; Christophe Robaglia; Alessandro Alboresi; Elodie Lanet (Plant Molecular Biology, 2013)

Development of COS-SNP and HRM markers for high-throughput and reliable haplotype-based detection of Lr14a in durum wheat (Triticum durum Desf.) - Irma Terracciano; Marco Maccaferri; Filippo Bassi; Paola Mantovani; Maria C. Sanguineti; Silvio Salvi; Hana Šimková; Jaroslav Doležel; Andrea Massi; Karim Ammar; James Kolmer; Roberto Tuberosa (Theoretical and Applied Genetics, 2013)

Mutagenesis and phenotypic selection as a strategy toward domestication of Chlamydomonas reinhardtii strains for improved performance in photobioreactors - Giulia Bonente; Cinzia Formighieri; Manuela Mantelli; Claudia Catalanotti; Giovanni Giuliano; Tomas Morosinotto; Roberto Bassi (Photosynthesis Research, 2011)

Parallel pigment and transcriptomic analysis of four barley Albina and Xantha mutants reveals the complex network of the chloroplast-dependent metabolism - Chiara Campoli; Stefano Caffarri; Jan T. Svensson; Roberto Bassi; A. Michele Stanca; Luigi Cattivelli; Cristina Crosatti (Plant Molecular Biology, 2009)

Coralline red algal assemblage from the Middle Pliocene shallow-water temperate carbonates of the Monte Cetona (Northern Apennines, Italy) - Alessio Checconi; Davide Bassi; Leonsevero Passeri; Roberto Rettori (Facies, 2007)

Photosynthesis research in Italy: a review - Giorgio Forti; Angela Agostiano; Roberto Barbato; Roberto Bassi; Enrico Brugnoli; Giovanni Finazzi; Flavio M. Garlaschi; Robert C. Jennings; Bruno Andrea Melandri; Massimo Trotta; Giovanni Venturoli; Giuliana Zanetti; et al. (Photosynthesis Research, 2006)

Formate binding near the redox-active TyrosineD in Photosystem II: consequences on the properties of TyrD - Rainer Hienerwadel; Samuel Gourion-Arsiquaud; Matteo Ballottari; Roberto Bassi; Bruce A. Diner; Catherine Berthomieu (Photosynthesis Research, 2005)

Recovery of carbonate platform production in the Lombardy Basin during the Anisian: paleoecological significance and constrain on paleogeographic evolution - Fabrizio Berra; Roberto Rettori; Davide Bassi (Facies, 2005)

Occurrence of the lutein-epoxide cycle in mistletoes of the Loranthaceae and Viscaceae - Shizue Matsubara; Tomas Morosinotto; Roberto Bassi; Anna-Luise Christian; Elke Fischer-Schliebs; Ulrich Lttge; Birgit Orthen; Augusto C. Franco; Fabio R. Scarano; Britta Frster; Barry J. Pogson; C. Barry Osmond (Planta, 2003)

Absorption spectra of chlorophyll a and b in Lhcb protein environment - Gianfelice Cinque; Roberta Croce; Roberto Bassi (Photosynthesis Research, 2000)

The Soret absorption properties of carotenoids and chlorophylls in antenna complexes of higher plants - Roberta Croce; Gianfelice Cinque; Alfred R. Holzwarth; Roberto Bassi (Photosynthesis Research, 2000)

Lhc proteins and the regulation of photosynthetic light harvesting function by xanthophylls - Roberto Bassi; Stefano Caffarri (Photosynthesis Research, 2000)

Isolation and characterization of chloroplast Photosystem II antenna of spinach by reversed-phase liquid chromatography - Lello Zolla; Anna Maria Timperio; Maria Grazia Testi; Maria Bianchetti; Roberto Bassi; Francesco Manera; Danilo Corradini (Photosynthesis Research, 1999)

Identification and characterization of photosystem II chlorophyll a / b binding proteins in Marchantia polymorpha L. - Roswitha Kilian; Roberto Bassi; Christian Schäfer (Planta, 1998)

The photosystem II subunit CP29 can be phosphorylated in both C3 and C4 plants as suggested by sequence analysis - Elisabetta Bergantino; Dorianna Sandonà; Daniela Cugini; Roberto Bassi (Plant Molecular Biology, 1998)

Selenium, zinc, and thyroid hormones in healthy subjects - Oliviero Olivieri; Domenico Girelli; Anna Maria Stanzial; Luigi Rossi; Antonella Bassi; Roberto Corrocher (Biological Trace Element Research, 1996)